Improving thermal diffusivity of supported Fe-based Fischer–Tropsch catalysts to enhance long-chain hydrocarbon production. Issue 7 (4th May 2021) - Xing, Chuang; Li, Mingquan; Fu, Yajie; Chen, Xiaobing; Lu, Peng; Li, Xiaotian; Amoo, Cederick Cyril
Abstract : Fischer Tropsch synthesis (FTS) is highly exothermic so heat removal remains crucial. In this study, a rational procedure is examined to remove heat in the FTS by improving the thermal diffusivity on a series of Fe-based catalysts. Abstract : Hydrocarbon fuels and other high-valued chemicals traditionally obtained from petroleum can be produced via the green and sustainable Fischer–Tropsch synthesis (FTS). However, the FTS reaction is highly exothermic which is suggested to have adverse effects on the overall performance of the catalysts. In this work, the effects of improved thermal diffusivity of the catalysts on FTS performance were investigated using pulverized aluminum (Al) mixed with SiO2 supported Fe catalysts. The Al content was varied and subsequent influence on the catalyst and product distribution was highlighted. By design, it was observed that the addition of Al barely influenced the intrinsic physicochemical properties of the basic Fe catalyst. However, it increases the thermal diffusivity of the catalyst which corresponded to an increased selectivity for long-chain hydrocarbons. These results directly clarify the influence of thermal diffusivity on catalytic activity and reveal a plausible path to efficiently reduce its impact on the FTS reaction.